Cenozoic stratigraphy of the Golfo San Jorge Basin (Argentina): an integrated record of tectonic, climatic, and eustatic controls on basin evolution (Latin American Journal of Sedimentology and Basin Analysis, 2025)
The Golfo San Jorge Basin (GSJB) preserves the thickest Cenozoic stratigraphic record in extra-Andean Patagonia (Argentina), reaching approximately 1500 meters. This record was subdivided into three major second-order transgressive regressive (TST-RST) sedimentary sequences: (1) The early Paleogene T-R cycle (~ 600 m thick; early Paleocene–late Eocene), comprising the Salamanca Formation (marine), Río Chico Group (fluvial), and part of Sarmiento Formation (pyroclastic loess). This sequence reflects a marine-to-continental transition, with an early marine stage marked by tidally-influenced, shallow-marine and inner-shelf sedimentation, followed by fluvial systems and long-lived accumulation and reworking of fine ash in a low-gradient continental setting. (2) The late Paleogene-early Neogene T-R cycle (~ 200 m thick, late Eocene-earlyMiocene), composed of the El Huemul Formation (marine) and the upper part of Sarmiento Formation (pyroclastic deposits). (3) The Neogene T-R cycle (~ 700 m thick; early–middle Miocene), includes the Chenque Formation (marine) and the Santa Cruz or Escalante Formation (fluvial-eolian). The three marine second order TSTs share similar temporal duration (
Keywords: second-order T-R sequences; Atlantic; Paleogene; Neogene; extra-Andean; Patagonia